Strategi Komite Olahraga Nasional Indonesia dalam Peningkatan Prestasi Cabang Olahraga Futsal di Kota Tangerang Selatan - Raihan Putra Pratama; Abdul Rahman (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research aims to find out and analyze the strategy of the Indonesian National Sports Committee in improving the achievements of the Futsal sport branch in South Tangerang City. This research uses Geoff Mulgan's theory (2009) with 5 indicators, namely goals, environment, direction, action, learning. The research method used in this research is descriptive with a qualitative approach. The results of the research show that the indicators aimed at KONI in South Tangerang City in order to optimize the increase in performance in the futsal sport are quite good. This is characterized by policies and programs created as a form of carrying out the management mission that is currently underway during the periodization period. In terms of internal environmental indicators, the strength of human resources must be able to continue to innovate in advancing sports, especially futsal. The people involved have potential in accordance with their duties and functions in creating strategies to manage the management of the futsal sport. Then the direction indicator shows that the important role that takes priority is the policy made by the General Chair. The general chairman makes a policy regarding the management strategy for the futsal sport, which must be followed by its members. In South Tangerang City Regional Regulation Number 7 of 2017 concerning the Implementation of Sports, however, currently, there is still no effective direction given to members involved in managing the sport of futsal. Action Indicators show that external situations must be addressed immediately before bad things happen. The strategies created will not fully run smoothly according to the plans and decisions taken jointly. Then the lesson here is that KONI South Tangerang City must change and evaluate its less than optimal performance.